Improving recruitment process for nurses, professions supplementary to medicine and paramedical staff - Pamila Sadeeka Adikari; Dileep De Silva; Sunil De Alwis; KYPK Weerasekara; Parmelalagapillai Karthikeyan; HHDAU Hettiarachchi; Kapuge Ranjith Kumara; HW Sunil Shantha (Journal of Health Technology Assessment in Midwifery, 2020)
The recruitment process of nurses, professions supplementary to medicine and paramedical staffs had been a lengthy and labourers work for the Ministry of Health and Indigenous Medical Services (MoHIMS) of Sri Lanka. The process affected the regular recruitment of mentioned staff categories. Flaws in this system contributed negatively to the country's shortage of human resources for health (HRH) as well as efforts to improve the healthcare service delivery. The aim of the study was to identify the gaps in the traditional paper-based recruitment system of the MoHIMS and to design a suitable intervention to improve the process and to assess the improvements brought about by the intervention. A service improvement project with full participation of stakeholders was planned by the Human Resource Coordination Division (HRCoD) of the MoHIMS. Qualitative methods were used to identify the gaps in the existing recruitment system and to gather the ideas for improvement. A computer based online recruitment system was implemented with the collaboration of the Department of Computer Science Engineering, Faculty of Engineering, University of Moratuwa. The perceived satisfaction of the stakeholders was reassessed by qualitative methods. Long lag between advertising and recruitment for training was revealed. Deficiencies such as, lack of transparency, negatively affected routine office processes, inability to validate examination results during application process and frustrated applicants leaving the training programs due to lengthy selection processes were also among the main gaps identified. The implemented online recruitment system was recognised by the stakeholders for its improved timeliness, transparency and minimal interference to the routine office functions. Service improvement projects to be successful, should be implemented with full stakeholder participation. Computer based online recruitment systems can be successfully implemented in public sector recruitments to improve the efficiency and transparency